Social Insurance in the Philippines: Responding to the Global Financial Crisis and Beyond - Rosario G. Manasan (Philippine Institute for Development Studies (PIDS), 2009)
This paper aims to review and assess protection afforded by the Social Security System and the Government Service Insurance System, two out of the three agencies tasked with administering social insurance in the country. Like social security systems in other countries, the GSIS and SSS provide income support to government/private sector employees and their families in times of contingencies like death, old age, sickness, and disability arising from work, and are financed out of the contribution of members and their employers. The GSIS and SSS are both mandatory, publicly managed, benefit-defined social insurance schemes with funding coming from members and their employers and investment income from reserves. Government guarantees the solvency of both systems and the levels of benefits prescribed. The global economic downturn will tend to reduce the stream of contributions to the social security system as a result of the increase in unemployment and the reduction in the level of earnings on which contributions are based. At the same time, there will be a temptation on the part of policymakers to use the pension funds to partially finance the fiscal stimulus package that has been drawn in response to the crisis. However, using the pension funds for the purpose of pump priming the domestic economy will likely not match the primary objective of the fund to protect old-age income of members. Even without the global financial crisis, reforms aimed at improving the financial viability of and corporate governance in both the GSIS and the SSS have already been started. Some gains have already been achieved in various areas of concern but sustained effort is still needed. The needed reforms have already been articulated by various experts (e.g., Holzmann et al. 2000, Navarro 2004, OECD 2009, Asher 2008) and includes: (i) the broadening of coverage and enhancement of compliance; (ii) greater emphasis on fiduciary responsibility of social security institutions and improve the management of their investment portfolio; and (iii) reduction in administrative cost; and (iv) institution of additional parametric measures to improve sustainability of the social security institutions and reduce the national government's contingent liability. Prospectively, there is a need to explore the feasibility of a noncontributory social pension for aged poor given the low coverage of the informal sector in the SSS.
Keywords: 330; defined-benefit social insurance scheme; replacement rate and required contribution rate of social security system; Finanzkrise; Finanzierung der Sozialversicherung; Philippinen